MAHMUDHOJA BEHBUDIY: REPRESENTATIVE OF THE JADIDIST MOVEMENT AND HIS FOLLOWERS (American Journal of Pedagogical and Educational Research, 2025)
This article discusses the importance of the Jadid movement in Central Asia and its emergence, the role of Mahmudkhoj Behbudi in the Jadid movement and its relevance, how their ideas were continued by their followers, and their significance today.